Isolation and identification of coliform bacteria from swimming pools / Khairunnisa Aqilah Kamarudin - Kamarudin, Khairunnisa Aqilah (2018)
The existence of coliform bacteria in water shows the potential presence of disease-causing bacteria in water an as an indicator of faecal contamination. The purpose of this study is to isolate and identify the presence of coliform bacteria in public swimming pools. The water samples were collected from indoor and outdoor swimming pools which are at Pusat Akuatik Stadium Hang Jebat and Kolam Renang Awam Majlis Bandaraya Melaka Bersejarah (MBMB) in Melaka. The procedure used to isolate and identify the presence of coliform was the convectional Multi Tube Fermentation (MTF) method. The gram staining procedure was done to verify the coliform’s morphology. The biochemical test gave a positive result for the presence of Escherichia coli.